2020
DOI: 10.1136/bmjopen-2020-042555
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress of the healthcare workforce during the COVID-19 pandemic evolution: a cross-sectional study in Spain

Abstract: ObjectivesTo determine the volume of health professionals who suffered distress due to their care of patients with COVID-19 and to analyse the direction in which the response capacity of the professionals to face future waves of COVID-19 is evolving.DesignA cross-sectional study.SettingPrimary care and hospitals in Spain.ParticipantsA non-randomised sample of 685 professionals (physicians, nurses and other health staff).Primary and secondary outcome measuresFrequency and intensity of stress responses measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 32 publications
3
73
0
6
Order By: Relevance
“…The EASE scale has sufficient sensitivity; the staff in contact with COVID-19 patients had higher levels of acute stress than other staff, as suggested in other studies [22]. When the EASE scale has been used in other studies, it was revealed that the levels of acute stress were higher in the absence of personal protective equipment, when the care pressure was greater, among professionals in critical or emergency units, and, as in this case, in those territories with a greater number of cases [23,24]. Since the current situation (ie, the third wave) seems different from the previous one, the scale's utility in the next 3 to 6 months, after the worst of the current health crisis, should be checked.…”
Section: Principal Findingssupporting
confidence: 67%
“…The EASE scale has sufficient sensitivity; the staff in contact with COVID-19 patients had higher levels of acute stress than other staff, as suggested in other studies [22]. When the EASE scale has been used in other studies, it was revealed that the levels of acute stress were higher in the absence of personal protective equipment, when the care pressure was greater, among professionals in critical or emergency units, and, as in this case, in those territories with a greater number of cases [23,24]. Since the current situation (ie, the third wave) seems different from the previous one, the scale's utility in the next 3 to 6 months, after the worst of the current health crisis, should be checked.…”
Section: Principal Findingssupporting
confidence: 67%
“…A more detailed overview of all investigated outcome measures can be found in Table 1 [ 3 , 8 ▪ , 10 , 11 ▪ , 12 ▪ , 13 , 14 ▪ , 15 20 , 21 ▪ , 22 ▪ , 23 , 24 , 25 ▪ , 26 , 27 , 28 ▪ , 29 ▪ , 30 , 31 34 ].…”
Section: Other Mental Health Aspectsmentioning
confidence: 99%
“…Moreover, these results show a similar trend con rming the fear of infecting the family and not being able to disconnect at the end of the shift the two consequences most often cited by professionals as signs of distress. The rst study in 4 Latin American countries using this same scale found, among professionals working in primary care, an overall average score of 9.5, slightly lower than that found in this study [23]. When making comparisons it is necessary to consider the incidence of COVID-19 in each of the countries as the level of acute stress has been directly related to care pressure [23].…”
Section: Discussionmentioning
confidence: 58%